Quality-Assured Analysis of PIK3CA Mutations in Hormone Receptor–Positive/Human Epidermal Growth Factor Receptor 2–Negative Breast Cancer Tissue: A Story About the Need for Proficiency Testing for High-Quality Molecular Biomarker Reporting in Precision Medicine - Schmidt, Carolin; Stöhr, Robert; Dimitrova, Lora; Beckmann, Matthias; Rübner, Matthias; Fasching, Peter; Denkert, Carsten; Lehmann, Ulrich; Vollbrecht, Claudia; Haller, Florian; Hartmann, Arndt; Erber, Ramona (Journal of Molecular Diagnostics, 2024)
In precision oncology, reliable testing of predictive molecular biomarkers is a prerequisite for optimal patient treatment. Interlaboratory comparisons are a crucial tool to verify diagnostic performance and reproducibility of one's approach. Herein is described the design and results of the first recurrent, internationally performed PIK3CA (phosphatidylinositol-4,5-bisphosphate 3 kinase catalytic subunit α) breast cancer tissue external quality assessment (EQA), organized by German Quality in Pathology GmbH and started in 2021. After the internal pretesting phase performed by the (lead) panel institutes, in both 2021 and 2022, each EQA test set comprised n = 10 tissue samples of hormone receptor–positive, human epidermal growth factor receptor 2–negative invasive breast cancer that had to be analyzed and reported by the participants. In 2021, the results were evaluated separately for German-speaking countries (part 1) and international laboratories (part 2). In 2022, the EQA was performed across the European Union. The EQA success rates were 84.6% (n = 11/13), 88.6% (n = 39/44), and 87.9% (n = 29/33) for EQA 2021 part 1, part 2, and EQA 2022, respectively. The most commonly used methods were next-generation sequencing and mutation-/allele-specific qualitative PCR-based assays. In summary, this recurrent PIK3CA EQA proved to be a suitable approach to obtain an international overview of methods used for PIK3CA mutation analysis, to evaluate them qualitatively, and identify the strengths and weaknesses of individual methods.
CRIS-Team Scopus Importer:2024-05-31